GAMBARAN KLINIS PASIEN FIBROADENOMA MAMMAE TERKAIT OBESITAS - SASKIA PUTRI NISRINA ZULKARNAIN; RINI SYAHRANI HARAHAP (JURNAL ILMIAH MAKSITEK, 2023)
Obesity is a disease characterized by abnormal or excessive fat accumulation in adipose tissue which can be a health risk. In young women, obesity can lead to benign breast tumors. The most common benign breast tumor is fibroadenoma mammae (FAM). Fibroadenoma mammae (FAM) is defined as a benign breast tumor in the form of a lump that can be moved (mobile), well-defined, with a firm consistency. Benign breast tumors are more common in young and post-menopausal women, this is related to high levels of estrogen in the blood which is a risk factor for breast lumps. A high body mass index (BMI) appears to be a substantial risk factor for the development of FAM, especially in young women. Other studies have shown high BMI is associated with a histopathological pattern of active FAM reflecting estrogenic stimulation; therefore, concluded that increased BMI was a significant risk factor for the formation of FAM. This study aims to determine the clinical manifestations in patients with fibroadenoma mammae associated obesity. This research uses a descriptive method using secondary data from medical records and primary data in the form of patient interviews in medical records. In this study there was a clinical manifestations in the form of age, the majority in the early adult group (51.9%). Based on the age of menarche, menstrual cycle and duration of menstruation, the most groups were found to be normal. Meanwhile, the majority of patients experienced mild pain in menstrual pain (63.0%) and breast pain (63.0%). The most common tumor size was ≤ 3cm (59.3%), with a springy consistency (100.0%). The proportion of body mass index in this study was mostly in the obese group I as much as 48.1%. Characteristics of mammary fibroadenoma by age, the majority in the early adult group. Based on the age of menarche, menstrual cycle and duration of menstruation, the most groups were found to be normal. Meanwhile, the majority of patients experienced mild pain in menstrual pain and breast pain. The most common tumor size is ≤ 3cm in size, with a springy consistency. The proportion of body mass index in this study was mostly in the obese group I